Review of the tribe Lethaeini Stål (Hemiptera: Heteroptera: Lygaeoidea: Rhyparochromidae) from China, with a key to Chinese genera and species - Li, Junlan; Gao, Cuiqing; Bu, Wenjun (Zootaxa, 2011)
The tribe Lethaeini Stål from China is reviewed. Seventeen species in seven genera are recognized. Four genera, Adauctus Distant, Atkinsonianus Distant, Lamproceps Reuter, and Lethaeus Dallas; and five species, Adauctus cupreus Distant, Atkinsonianus reticulatus Distant, Lamproceps antennatus (Scott), Lamproceps bipunctatus (Bergroth), and Lethaeus taprobanes Kirkaldy are reported for the first time from China (new records). Diniella yinae Zheng & Liu is treated as a junior synonym of Lamproceps antennatus (Scott) (new synonymy). A key to Chinese genera and species of the tribe is given. Diagnoses of the genera, habitus photos, male genitalia illustrations, additional distributions, biology (if possible), and taxonomic remarks of the species are also presented.